PENGOLAHAN AIR LIMBAH INDUSTRI ELEKTROPLATING DENGAN ELEKTROKOAGULASI MENGGUNAKAN ELEKTRODA Fe - Jessica Dima F.M.; Maulida Zakia; R Ratnawati (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Electroplating industry is one of industry that still growing in Indonesia. The wastewater generated from this industry is dangerous because it contained  dissolved metals such as chromium, nickle, cadmium, copper, etc. Currently,  there are some wastewater treatment method such as presipitation, microorganism, ultrafiltration, and reverse osmosis. However those method has disadvantage like secondary wastewater, high cost, and applied on industry scale is hard. The more effective method is electrocoagulation. In this research potassium dichromate solution is used as sintetic wastewater and tested on electroplating wastewater. Electrocoagulation method will be investigated by studying the effect of time, initial concentration and current density to the TDS of final solution. In the electroplating wastewater tested the effect of time and current density to the TDS of final wastewater. Iron Fe ST 37-2 are used as electrodes. From this research obtained that on the low initial concentration of potassium dichromate will give higher removal TDS (77,78%) than on the higher initial concentration (41,18%). This is because at the same time frame the number of Fe2+ produced not enough to reduce all Cr6+ in solution with high concentrations. In the high current density gave higher removal TDS (65,95%) than low current density (34,48%). The higher current density indicates the more Fe2+ produced to reduce Cr6+ to Cr3+ that will form Cr(OH)3 so it can deposited easily. Electrocoagulation method can be applied to wastewater  because it can lower the TDS of electroplating wastewater by using a variation of current density.